Gender differences in submission strategies? A survey of early-career economists - Christina Gravert; Katrine Thornfeldt Sørensen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
We investigate whether the gender gap in economic publications can be explained by different submission strategies of male and female economists. We conduct an online survey among early-career economics faculty of top 50 institutions focusing on the submission trajectories of job market papers as well as personal and institutional characteristics. Our results suggest that there are no significant differences in submission strategies for this early-career sample.
Keywords: D04; D83; D91; J16; 330; gender bias; economists; publications; survey